Ship to shore [compact disc] - Thompson, Richard, 1949- (New West Records, 2024)
When Richard Thompson began writing songs for his latest album, the artist was instinctively drawn to his own musical roots, employing them in the service of fashioning a deep and diverse 12-track collection that pulls from various styles, genres, and eras but remains unmistakably Richard Thompson.